The Results of Whole Exome Sequencing Performed On Previously Undiagnosed Pediatric Neurology Patients - Ahmadnia, Negin; Beiraghitoosi, Mehran; Ghayour karimiani , Ehsan; Ashrafzadeh, Farah; Faraji rad, Mohammad (Iranian Journal of Child Neurology, 2021)
Objective Whole exome sequencing (WES) is a new molecular diagnostic test, used in pediatric medicine, especially pediatric neurology. The diagnostic yield of WES is higher than conventional methods. Therefore, this study aimed to assess the diagnostic yield of WES in a pediatric neurology clinic and to report positive results. Materials & Methods This retrospective study was performed on patients, presenting to the pediatric neurology clinic of Ghaem Hospital in Mashhad, Iran, between March 2015 and March 2017, with various neurological disabilities and unrevealing workup before WES. The patients’ clinical features and molecular diagnoses based on the WES Results were reported in this study. The overall diagnostic yield of WES was 82.71% (67/81 patients). Two patients were excluded for the lack of data. Sixty-five patients with pathogenic or possibly pathogenic variants exhibited various abnormalities, including intellectual disability/developmental delay (n=44), seizure (n=27), developmental regression (n=11), myopathy (n=9), microcephaly (n=8), neuropathy (n=2), autism spectrum disorder (n=2), and neuromuscular disease (n=2). Overall, 93.84% of the patients were born to consanguineous parents. Also, 62 patients had an autosomal recessive disorder, and three patients had an autosomal dominant disorder. Conclusion The present findings indicating the high diagnostic yield of WES, besides the important role of this test in determining the etiology of non-specific and atypical presentations of genetic disorders, support the use of WES in pediatric neurology practice.